Go-To-Market Strategy And Customer Value Proposition Assistance To Increase Competitive Advantage Of Textile MSMEs - Muhammad Iqbal Alamsyah; Deden Syarif Hidayatulloh; Candiwan Candiwan (Universitas INABA, 2026)
Textile MSMEs in Bandung face increasingly intense competition due to penetration of cheap imported products, changes in digital consumer behavior, and growing competition on marketplace platforms. The main problems faced include a weak customer value proposition (CVP), unstructured marketing funneling, and the absence of a go-to-market (GTM) strategy grounded in competitive advantage. This community service activity aims to improve the strategic capacity of textile MSMEs through assistance in formulating customer value propositions, designing marketing funneling based on customer journey, and developing segmented and positioning-based go-to-market strategies. The activity was carried out with 19 textile MSME participants at CV. Million Bandung Indonesia, Arcamanik District, Bandung City, from March to June 2026. The implementation method used a participatory approach through stages of baseline assessment, workshop, coaching and business mentoring, implementation, and monitoring and evaluation. Post-activity survey results showed that 92–100% of the 19 participants strongly agreed that the program materials, duration, and facilitation met their needs, while five core management personnel received intensive one-on-one mentoring to translate the strategic frameworks into business-specific action plans. Results show that participants were able to identify main customer segments, formulate clearer value propositions, develop more structured marketing strategies, and establish simple marketing performance indicators. Program outputs include a practical module on marketing funneling and go-to-market strategy, a marketing KPI dashboard, and improved partner capabilities in designing data-based marketing strategies.